Understanding Music as a Mathematical Activity through Chrome Music Lab - Mishra , Kumar Gandharv (Indian Journal of Educational Technology, 2021)
The paper is an attempt to present some (four) Experiments of Chrome Music Lab in the context of mathematics. The activities suggested in the paper can be used by teacher-students as a pedagogical tool to understand music as a mathematical activity as well as to explore and work on some mathematical concepts as a part of music composition. The activities discussed in the paper can also be worked upon by the general public, parents, mathematics and music enthusiasts, and educators to understand and communicate music as a mathematical activity in an interactive manner.